Analysis of Sport Tourism Potential in Pasir Kencana Beach, Pekalongan City - Susanti, Devi; Raharjo, Agus (Universitas Negeri Semarang, 2025)
This research analyzes the potential for sport tourism in Pantai Pasir Kencana, located in Pekalongan City, Central Java, Indonesia. The objectives include: (1) identifying the current conditions of sport tourism facilities and infrastructure; (2) examining the challenges and limitations in the development process; and (3) mapping potential through a SWOT analysis framework. The study employs a qualitative descriptive method, involving data collection through observation, interviews, and documentation. Data validity was ensured through triangulation. The findings reveal that while infrastructure renovation has enhanced the area's appeal, many sport-specific facilities remain underdeveloped. Furthermore, its growth is hindered by a lack of promotional efforts, limited organized sports events, and weak stakeholder collaboration. Despite these, the site holds strong potential due to its location, cultural assets, and visitor interest. Recommendations include strategic planning, community engagement, and enhancement of sport-related infrastructure to foster sustainable sport tourism